Prevalance and molecular epidemiology of clostridium difficile infection in Hospital Universiti Sains Malaysia patients and elderly community subjects in Kelantan - Zainul, Nadiah Hanim (2016)
Introduction An increase in the incidence of Clostridium difficile infection (CDI) in Western countries has come to prominence over the last 15 years. However awareness and surveillance of CDI in Asia remained poor with epidemiological data being scanty in Asia and in particular Malaysia. CDI is commonly associated with nosocomial infections, but community acquired CDI has been reported with increasing frequency lately. Despite the increase in incidence and severity of CDI, a recent survey found awareness of CDI being poor, with underestimation of its contribution to antibiotic-associated disease and recurrence rates. Objective We aimed to explore the prevalence and associated risk factors of CDI in hospitalized patients in HUSM. We also aimed to explore the carriage rate among the elderly in the community in Kelantan. Finally we aimed to determine the level of awareness of CDI among staff and students in HUSM. Methodology This study is divided into 3 arms. For the hospital arm, it was a prospective cross sectional study of CDI prevalence among 76 hospitalized patients in HUSM from 1st April 2015 until 30th September 2015. For the community arm, it was a cross sectional study of C. difficile carrier prevalence among 138 elderlies from the community in Kelantan from July 2015 to September 2015.For both arms, stools were tested for C. difficile antigen and toxin detection using C. DIFF QUIK CHEK COMPLETE®. The samples were then sent to Western Australia for culture and PCR for toxin genes and ribotyping for molecular epidemiology. For the awareness survey, it was a cross sectional study of C. difficile awareness among 154 participants comprised of HUSM staff and students during an awareness campaign for C. difficile in HUSM on 6th August 2015. Data was obtained thru a self-administered questionnaire which was based from a previous international internet-based awareness study. Result For the hospital arm, 20 samples (26.3%) were positive for C. difficile antigen (CDifAg), 7 samples (9.2%) were positive for C. difficile toxin (CDifToxin) and 19 samples (25%) were positive from direct culture. Significant ribotype diversity with six distinct ribotype groups (QX001, UK 017, QX 002, QX 107, QX 117 and QX 463) were identified. Charlson Comorbidity Index, urea, creatinine, albumin and CRP level, duration of hospitalization, use of antibiotics, use of chemotherapy, underlying medical illness and fulminant severity were significantly associated with CDI using Simple Logistic Regression (P-value < 0.25). Further analysis with Multiple Logistic Regression showed significant association between CDI with age, duration of hospitalization and use of antibiotics (P-value < 0.05). For the community arm, 2 samples (1.6%) were positive for both CDifAg and direct culture while negative for CDifToxin. Ribotying of the 2 samples showed unknown strain. From the study, it was found that the study population did not have high PPI and antibiotics use which were known CDI risk factors. For awareness study arm, there was a low level of awareness on CDI with only 2.6% of 154 respondents able to correctly answer all questions correctly. Ironically a large proportion of the participants (n = 73; 47.4%) considered C. difficile to be overestimated in their current practise. There was no significant association between level of awareness on CDI with age, gender and occupation i.e. being a clinician. Conclusion In conclusion, this study demonstrated that the prevalence rate for CDI in hospitalized patients in HUSM were 26.3% for CDifAg, 9.2% for CDifToxin and 25% for direct culture with 6 distinct ribotype strains; QX001, UK 017, QX 002, QX 107, QX 117 and QX 463 identified. Independent risk factors for CDI were age, duration of hospitalization and use of antibiotics. The carrier rate for C. difficile was 1.6% among the elderly in the community with unknown strain identified from PCR ribotyping. Low usage of PPI and antibiotics were seen in our study population and could explain the low prevalence rate of CDI in our study population. Low awareness on CDI was seen among healthcare professionals in HUSM which was also seen internationally. Therefore CDI being an underdiagnosed and under recognised issue in the healthcare system is an issue that needs to be addressed by all parties.